ANALISIS KUALITAS LIMBAH CAIR DI RUMAH POTONG HEWAN (RPH) PEKANBARU SEBAGAI RANCANGAN HANDOUT MATERI LIMBAH DAN PENGELOLAAN LIMBAH DI SMA KELAS X - Efendi, Lilik; Darmawati, Darmawati; Fauziah, Yuslim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aimed to determine the quality of liquid waste in PekanbaruAnimal Slaughterhouse and produced a handout the topic of waste and wastemanagement for Senior High School grade X. This research was conducted in the Ecology and Aquatic Environment Management Laboratory of Fisheries and Marine Faculty, Experiment and Analysis Laboratory of Chemical Engineering, Microbiology Laboratory of Medical Faculty at Riau University. The sample of this research was taken at waste water treatment plantin PekanbaruAnimal Slaughterhouse.The research was conducted on May until November2019. This research was conducted in two stages, namely analysis stage of liquid waste quality in PekanbaruAnimal Slaughterhouseand design a handout stage.The technique of data retrieval was conducted by using exploratory research, survey method for collecting the data, technique of determine the sample was purposive sampling. The parameters of this research were total coliform, BOD, COD, TSS and ammonia. The result showed that the liquid waste quality of PekanbaruAnimal Slaughterhouseoverall classified was not good where the total coliform, TSS, BOD, and COD gotresults more than the quality standards and the ammonia parameter of liquid waste was appropriate with the quality standards required by the Minister of Environment Regulation Number 5 of 2014. Based on analysis of the result, there was designed a handout the topic of waste and waste management for Senior High School grade X.Key Words: Animal Slaughterhouse, Handout, Liquid Waste